PENGEMBANGAN MEDIA PEMBELAJARAN SAINS TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN - Anita Roslina Simanjuntak; Jane Koswojo; Sindy Anugerah Wati (IKIP Siliwangi, 2022)
This study aims to create and develop science learning media that can be used to stimulate aspects of cognitive development of children aged 5-6 years to help educators to convey material so that children also more easily understand the material presented by educators. The research was carried out on children aged 5-6 years in the even semester of the 2021/2022 academic year. Learning media is made in the form of Children's Worksheets (LKA), in which there are various science experiment activities for children aged 5-6 years. The type of research used is research and development (R and D), the research model used is the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation) which was adapted from Branch. The data collection techniques used were observation and questionnaires to determine the development of early childhood science learning media. Data analysis used effectiveness data analysis to determine the effectiveness of using science learning worksheets as stimulation of cognitive development aspects. The results of the effectiveness of using the development of science learning worksheets in 12 children obtained an average score of 87%. The score results are included in the